Epidemiology of Ebola virus disease transmission among health care workers in Sierra Leone, May to December 2014: a retrospective descriptive study. Issue 1 (December 2015) - Olu, Olushayo; Kargbo, Brima; Kamara, Sarian; Wurie, Alie; Amone, Jackson; Ganda, Louisa; Ntsama, Bernard; Poy, Alain; Kuti-George, Fredson; Engedashet, Etsub; Worku, Negusu; Cormican, Martin; et al.
Abstract Background Anecdotal evidence suggests that much of the continuing infection of health care workers (HCWs) with Ebola virus during the current outbreak in Sierra Leone has occurred in settings other than Ebola isolation units, and it is likely that some proportion of acquisition by HCWs occurs outside the workplace. There is a critical need to define more precisely the pathways of Ebola infection among HCWs, to optimise measures for reducing risk during current and future outbreaks. Methods We conducted a retrospective descriptive study of Ebola acquisition among health workers in Sierra Leone during May–December 2014. The data used were obtained mainly from the national Ebola database, a cross-sectional survey conducted through administration of a structured questionnaire to infected HCWs, and key informant interviews of select health stakeholders. Results A total of 293 HCWs comprising 277 (95 %) confirmed, 6 (2 %) probable, and 10 (3 %) suspected cases of infection with Ebola virus were enrolled in the study from nine districts of the country. Over half of infected HCWs (153) were nurses; others included laboratory staff (19, 6.5 %), doctors (9, 3.1 %), cleaners and porters (9, 3.1 %), Community Health Officers (8, 2.7 %), and pharmacists (2, 0.7 %). HCW infections were mainly reported from the Western Area (24.9 %), Kailahun (18.4 %), Kenema (17.7 %), and Bombali (13.3 %) districts. Almost half of the infected HCWs (120, 47.4 %) believed that their exposure occurred in a hospital setting. Others believed that they were exposed in the home (48, 19 %), at health centres (45, 17.8 %), or at other types of health facilities (13, 5.1 %). Only 27 (10.7 %) of all HCW infections were associated with Ebola virus disease (EVD) isolation units. Over half (60 %, 150) of infected HCWs said they had been trained in infection prevention and control prior to their infection, whereas 34 % (85) reported that they had not been so trained. Conclusions This study demonstrated the perception that most HCW infections are associated with general health care and home settings and not with dedicated EVD settings, which should provide substantial reassurance to HCWs that measures in place at dedicated EVD facilities generally provide substantial protection when fully adhered to.